Comparative Analysis: The Effects of Reciprocal Teaching Model and Problem Based Learning Assisted by Pictorial Riddles on Students’ Critical Thinking - Putri, Iin Dwian; Fujiaturrahman, Sukron; Muhdar, Syafruddin; Jacob, Filgona (MIMBAR PGSD Undiksha, 2024)
The process of learning, it is imperative to actively engage every student to achieve the learning objectives. However, many schools still employ lecture-based methods without incorporating engaging instructional models, thereby failing to capture students' attention. To address this issue, the implementation of appropriate teaching models and captivating learning media is essential to motivate students in the teaching and learning process. The aim of this research is to analyze the comparative impact of the reciprocal teaching model and the problem-based learning model assisted by pictorial riddle media on the critical thinking abilities of elementary school students. This study utilizes a quasi-experimental method with a quantitative approach, employing the Pre-test-Post-test Control Group Design. The research population comprises all fifth-grade students, totaling 52 students, involving two classes. From this population, a sample of 26 students from each class was selected. The results of the experiment 1 class indicate hypothesis testing with a two-tailed t-test yielding a significance value of 0.000, which is less than 0.05 (0.000 < 0.05). Meanwhile, in the experiment 2 class applying the problem-based learning model, a Sig. t value of 0.000 < probability 0.05 was obtained. Consequently, this difference confirms a significant influence of each model on the enhancement of critical thinking abilities. Based on these findings, it can be concluded that the problem-based learning model has a more pronounced effect on improving critical thinking abilities compared to the reciprocal teaching model.